Space, site, intervention : situating installation art - Suderburg, Erika (London : University of Minnesota press, 2000)
Acconci, Vito ; Andre, Carl ; Asher, Michael ; Barry, Robert ; Broodthaers, Marcel ; Buren, Daniel ; Burr, Tom ; Campbell, Jim ; Campus, Peter ; Coleman, John ; Conner, Bruce ; Cornell, Joseph ; Deleuze, Gilles ; Dion, Mark ; Divola, John ; Duchamp, Marcel ; Riverhead (New York) ; Foster, Hal ; Gamboa Jr., Harry ; Gordon, Douglas ; Graham, Dan ; Green, Renée ; Guattari, Félix ; Haacke, Hans ; Hall, David ; Finlay, Ian Hamilton ; Hammons, David ; Heizer, Michael ; Hill, Gary ; Holt, Nancy ; Holzer, Jenny ; Jonas, Joan ; Judd, Donald ; Kabakov, Ilya ; Kapoor, Anish ; Kaprow, Allan ; Kienholz, Ed ; Kienholz, Nancy Reddin ; Kosuth, Joseph ; Levine, Les ; LeWitt, Sol ; de Maria, Walter ; Morris, Robert ; Nauman, Bruce ; Oppenheim, Dennis ; Osorio, Pepón ; Owens, Craig ; Paik, Nam June ; Piper, Adrian ; Rousseau, Jean-Jacques ; Serra, Richard ; Serrano, Andres ; Smithson, Robert ; Thater, Diana ; Tinguely, Jean ; Turrell, James ; Warhol, Andy
boek